Exploring Teacher Reflection in the English as a Foreign Language Context: Testing Factor Structure and Measurement Invariance - Xiaojing, Xing; Badakhshan, Ebrahim; Fathi, Jalil (Frontiers in Psychology, 2022)
The current study aimed to verify the multidimensional factor structure of teacher reflection and to examine the psychometric properties of a slightly adapted teacher reflection scale using a large-scale representative dataset of 1611 practicing Iranian English as a Foreign Language (EFL) teachers. Furthermore, the measurement invariance of the hypothesized, a priori six-factor model of teacher reflection as measured by the adapted scale was assessed across gender and educational degree in Mplus program. In addition, the differences in latent factor means of the same groups were examined. The result of confirmatory factor analysis revealed that teacher reflection was a multidimensional construct, encompassing six underlying factors. Overall, the adapted teacher reflection scale based on the 6-factor model showed an overall good fit. The results also indicated metric and scalar invariance which manifests that the constructs underlying the adapted scale possessed the same theoretical structure across educational degree/gender groups. Finally, there were significant factor mean differences in reflection components across gender and educational degree groups. A discussion of the results and their implications ensue.